(untitled) (Journal of Bangladesh Institute of Planners, 2019)
Paratransit often provides demand responsive and flexible transport service. Due to lack of formal public transport or mass transit system, particularly in medium or small-sized cities in Bangladesh, people are mainly dependent on paratransit for their mobility. The purpose of this paper is to provide operational characteristics of E-rickshaws (battery operated three wheelers) in urban transportation of Bangladesh. Questionnaire interview of 397 drivers of E-rickshaws in Rangpur city as well as a Focus Group Discussion (FGD) with the owners and members of the association of E-rickshaws were conducted for collecting data regarding physical and operational characteristics. Compared with other modes such as rickshaws, auto-tempo or minibus, E-rickshaws provide several benefits to the passengers. It was found that most of the E-rickshaw operators tend to make short trips only within the city. The average daily income generated by E-rickshaw is Tk 850 and income-expenditure ratio for the driver-owned operating E-rickshaw is 1.45. The findings of this paper may help the government and relevant agencies to formulate policy guidelines for the paratransit, especially when the mass transit system is on the transport planning menu. JBIP, Vol. 12, 2019 (Printed in June 2020), pp. 45-62